Experimental demonstration of complete quantum information masking and generalization of quantum secret sharing - Zhi-Feng Liu; Wei-Min Shang; Jia-Min Xu; Zi-Mo Cheng; Wen-Zheng Zhu; Hao Li; Pei Wan; Shu-Tian Xue; Yan-Chao Lou; Chao Chen; Zhi-Cheng Ren; He Lu; et al. (Communications Physics)
Abstract Quantum information masking (QIM) allows encoding quantum information in multipartite systems. Complete QIM is of great significance in quantum foundation and application. However, the realization of complete QIM, even for single-qubit encoded information, is still lacking. Here, we propose to demonstrate complete QIM with 4-qubit entangled states. The proposed QIM can be readily extended to multipartite systems with arbitrary number of subsystems, enabling quantum secret sharing (QSS) and quantum teleportation between multiplayers. In experiment, we build up a 4-qubit hyperentangled state to implement complete QIM. The trace distance of 16 encoded single-qubit states falls within the range of 0.12 ± 0.02 to 0.03 ± 0.02. Furthermore, we implement QSS between six players by expanding the 4-qubit state to a 6-qubit state entangled in hybrid manner, in which we observe an average fidelity 0.85 ± 0.03 of the recovered states. Our results open the door towards QIM-enabled quantum information processing and provide applications in quantum communications.